Using Ms Excel Function to Solve Economic Problems - Gulshoda Shodmonkulovna Qudratova (Indonesian Journal of Innovation Studies, 2022)
The paper discusses the main and frequently used formulas in Excel for use in the field of economics: IF, SUMIF, VLOOKUP, SUMPRODUCT, COUNT, AVERAGE, MAX, MIN.